2006
DOI: 10.1167/iovs.05-1078
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative Facility in Eyes with and without Myopia

Abstract: Myopic eyes have reduced accommodative facility at distance, and accommodative responsiveness to both positive and negative defocus is slow. However, accommodative facility as a test does not have sufficient power to discriminate eyes with myopia from other refractive errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 36 publications
8
39
3
1
Order By: Relevance
“…They reported reduced rates in myopes, but this difference was only significant at distance (9.7 cpm for myopes and 15.7 cpm for emmetropes). A similar result has been reported by Pandian et al 32 in a large sample of school children (1328 total; 977 emmetropes, 331 hyperopes, and 20 myopes). Furthermore, in a more recent investigation, Allen and O'Leary 33 investigated various accommodative functions to determine the natural progression of refractive error in 64 young adults (30 myopes and 34 non-myopes) during a period of 12 months.…”
Section: Discussionsupporting
confidence: 88%
“…They reported reduced rates in myopes, but this difference was only significant at distance (9.7 cpm for myopes and 15.7 cpm for emmetropes). A similar result has been reported by Pandian et al 32 in a large sample of school children (1328 total; 977 emmetropes, 331 hyperopes, and 20 myopes). Furthermore, in a more recent investigation, Allen and O'Leary 33 investigated various accommodative functions to determine the natural progression of refractive error in 64 young adults (30 myopes and 34 non-myopes) during a period of 12 months.…”
Section: Discussionsupporting
confidence: 88%
“…The accumulative effects of accommodation eventually cause the structural elongation of the eyeball in the myopic eye. [22][23][24] Our study showed a decrease in AA postoperatively, and CT increased as AA reducing after surgery. We proposed that after correcting the refractive error, retinal images become clearer.…”
Section: Discussionmentioning
confidence: 49%
“…We postulated that there may be two major reasons as followings: (1) poor accommodative facility and slow accommodative responsiveness were existed in myopic people with accommodative lag, 24,25 which would result in low accommodation reserve of myopia patients. (2) Accommodation demand was increased at the early postoperative period because of post apex moved backward to cornea and overcorrection early postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have suggested that various oculomotor factors may be related to the development, progression, and stabilization of myopia including poor accommodative response [2–8], decreased accommodative tonus [9], decreased accommodative amplitude [10], reduced accommodative facility [1113], increased accommodative adaptation [14], increased accommodative variability [15], near phoria [16], and AC/A ratio [8, 17, 18]. Both animal [19, 20] and human [3, 21] research have led to the development of a theory referred to as the “blur hypothesis.” This theory suggests that retinal defocus caused by underaccommodation may be a factor related to myopia development and progression [3, 21].…”
Section: Introductionmentioning
confidence: 99%